Increasing Ball Velocity in the Overhead Athlete: A Meta-analysis of Randomized Controlled Trials. Issue 10 (October 2015) - Myers, Natalie L.; Sciascia, Aaron D.; Westgate, Philip M.; Kibler, William B.; Uhl, Tim L.
Abstract : Abstract: Myers, NL, Sciascia, AD, Westgate, PM, Kibler, WB, and Uhl, TL. Increasing ball velocity in the overhead athlete: a meta-analysis of randomized controlled trials. J Strength Cond Res 29(10): 2964–2979, 2015—Overhead athletes routinely search for ways to improve sport performance, and one component of performance is ball velocity. The purpose of this meta-analysis was to investigate the effect of different strengthening interventions on ball and serve velocity. A comprehensive literature search with pre-set inclusion and exclusion criteria from 1970 to 2014 was conducted. Eligible studies were randomized control trials including the mean and SD s of both pretest and posttest ball velocities in both the experimental and the control groups. The outcome of interest was ball/serve velocity in baseball, tennis, or softball athletes. Level 2 evidence or higher was investigated to determine the effect different training interventions had on velocity. Pretest and posttest data were extracted to calculate Hedges's g effect sizes with 95% confidence intervals (CIs). Methodological qualities of the final 13 articles within the analysis were assessed using the Physiotherapy Evidence Database scale. The majority of the articles included in this analysis had an effect on velocity with the strongest effect sizes found in periodized training (Hedges's g = 3.445; 95% CI = 1.976–4.914). Six studies had CI that crossed zero, indicating that those specific interventions should be interpreted with caution. Consistent and high-quality evidence exists that specific resistance training interventions have an effect on velocity. These findings suggest that interventions consisting of isokinetic training, multimodal training, and periodization training are clinically beneficial at increasing velocity in the overhead athlete over different windows of time.